TEKNIK PENYUSUNAN LAPORAN KEUANGAN BAGI KSPPS/USPPS KOPERASI SYARIAH DI KALIMANTAN SELATAN - Syafril Djaelani (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2020)
Community service is carried out by providing training on financial report preparation techniques for KSPPS / USPPS cooperatives in the South Kalimantan region. Accounting is an information system that produces financial reports to interested parties. Accounting knowledge is useful to reduce the risk of errors in recording. Based on the explanation that the cooperative activity is selling services and other activities. Cooperative activities are also carried out in several Islamic cooperatives in Banjarmasin. Knowledge of accounting is very necessary for the successor and members to avoid fraud and can minimize the risk of recording the transaction activities that occur in the cooperative. This activity uses a descriptive qualitative approach. The method used is cerama (presentation), interactive dialogue and question and answer. Hopefully this activity will provide benefits to the management and members of cooperatives in the South Kalimantan region